A cognitively valuable reminder and memory of Vojin Milić’s sociological contribution - Milošević, Božo (Sociološki pregled, 2023)
This opinion/review deals with a valuable collection of sociological articles that were previously presented at an especially organised scientific meeting at the Institute for Sociological Research of the Faculty of Philosophy, University of Belgrade, which was held in September 2022, to honour 100th anniversary of the birth of Vojin Milić, an influential Serbian (and former Yugoslav) sociologist. The authors of these articles are predominantly younger-generation sociologists, whose professors were Milić’s former undergraduate students, master or doctoral students.In the nine original articles that these proceedings contain, the scientific contributions of Vojin Milić are systematically analysed in five key areas of sociology (sociological theory, history of sociological thought, methodology of sociological research, sociology of knowledge, and sociology of science). The authors of the articles presented in a very structured, systematic and critical manner some of Milić’s most important views, which make him recognisable among sociologists even after more than a quarter of a century since his passing.It is indisputable that they made a valuable effort to reaffirm what is most noteworthy from the domestic cognitive (sociological) legacy, which contributed to international reputation of Serbian sociology and thus allowed for a more substantial and comprehensive introduction of it to the domestic younger generations in science.